STUDY OF WOOD SAWDUST WITH ADDITION OF PLANTATION WASTES AS A GROWTH MEDIUM ON YIELDS AND QUALITY OF WHITE OYSTER MUSHROOM - Mudakir, Imam; Hastuti, Utami Sri (AGRIVITA, Journal of Agricultural Science, 2015)
The study aimed to investigate the use of wood sawdust as a medium for growth and the optimum addition ratio of plantation wastes that can increase the yields and quality of white oyster mushroom (Pleurotus ostreatus). This research used Completely Randomized Design (CRD) consisting of 7 levels of treatment ratio of Â wood sawdust and plantation wastes. The data analysis involved one way ANOVA followed by Duncanâs 5%. The results showed that the wood sawdust can be used as growing medium, and the addition of plantation wastes can increase the yields and the quality of white oyster mushroom. The addition of cocoa and coffee wastes with a ratio 25% was the optimum ratio treatment which increased the number of fruiting bodies, caps diameter, production weight, Biologycal Eficiency Ratio (BER) and protein, fats, carbohydrates and fiber content in white oyster mushrooms. It is recommended to be applied because both treatments would increase the yield and quality of white oyster mushroom.Keywords: cocoa and coffee pods wastes, wood sawdust, yield and quality of white oyster mushroomÂ Â Â